Pre-colonial residuals in Toni Morrison's Recitatif and Alice Walker's Everyday Use - Abu Jweid, Abdalhadi Nimer Abdalqader; Termizi, Arbaayah Ali; Moghadam, Nahid Shahbazi (Universiti Putra Malaysia Press, 2015)
This article examines Toni Morrison's Recitatif and Alice Walker's Everyday Use as post-colonial texts. Morrison's short story moves beyond the postcolonial aftermath to maintain pre-colonial cultural conventions. The discussion begins with how Recitatif is considered within the field of postcolonial studies, demonstrating such postcolonial concepts as diaspora, nativism and chromatism. The study also focuses on Alice Walker's short story Everyday Use, and discusses how various forms of Filiation/Affiliation and Synergy contribute to the conventions of precolonial culture. Everyday Use aims precisely at ethical propensity within colonial circumference. Thus, Walkerself-consciously illustrates the level of its pre-colonial features, which expose the colonisation dispersal of identity.